Pengguron Sunan Gunung Jati Abad XV-XVI M - Rido, Rosidi (IAIN Syekh Nurjati Cirebon, 2024)
Pengguron, a medieval Islamic educational institution, was first introduced by Sheikh Hasanuddin from Mecca in 1418 in Cirebon. This institution, which can be traced back to before the birth of Syarif Hidayatullah in 1448, was originally established as a madrasa, or Islamic school, in 1448. Pengguron exhibits a variety of formats and specialized elements, including tajug, students, rama guru, baiat, and witana. This research elucidates the perspectives of functionalism, power politics, and Tarekat Syattariyah to examine the Pengguron of Sheikh Nurjati through heuristic research methods. It describes the genesis of the Pengguron, which was motivated by Subang Larang, who ordered his children to study Islam in the Pengguron of Sheikh Quro, Karawang, and the Pengguron of Sheikh Nurjati Pasambangan. Furthermore, the Pengguron served as a hub for Islamic propagation, evolving not only into an educational institution but also a political force during its historical period. For this reason, the Pengguron has a curriculum in the form of the sayings of Sunan Gunung Jati, as well as a student recruitment process and the development of Tarekat Syattariyah through the teachings of wirid nafi isbath, zikir sir, zikir syughul, sunnah prayer, sunnah fasting and prayer, which collectively form the foundation of Islam. This foundation is comprised of three key elements: faith, worship and ihsan.